View of Independence Square, Port of Spain, Trinidad W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
This is Independence Square of the late 1960s. Vintage cars are parked in the distance. Some bustle around the roundabout, with its statue. The largely concrete, khaki-coloured building in the background might be the Treasury building.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Historic buildings; Automobiles; Statues; 1969